Bone cells in cultures on nanocarbon‐based materials for potential bone tissue engineering: A review (Phys. Status Solidi A 12∕2014). Issue 12 (December 2014) - Bacakova, Lucie; Kopova, Ivana; Stankova, Lubica; Liskova, Jana; Vacik, Jiri; Lavrentiev, Vasily; Kromka, Alexander; Potocky, Stepan; Stranska, Denisa
<x xml:space="preserve">Abstract</x> Carbon nanoparticles are promising materials for application in bone tissue engineering. These nanoparticles can be applied as biomaterial coatings or as a component of three‐dimensional porous or fibrous scaffolds. The review by Bacakova et al. (pp. 2688–2702) is focused on (i) fullerene C60 and hybrid C60/Ti films in fresh (one week old) and aged (one year old) form, (ii) composites of synthetic polymers and carbon nanotubules (i.e., carbon nanohorns and carbon nanotubes), (iii) graphenebased materials (films and three‐dimensional scaffolds), and (iv) nanocrystalline diamond‐based materials (films and nanofibrous scaffolds loaded with nanodiamond particles). In general, all these substrates provided good supports for colonization with human bone cells in the form of cell lines, primary osteoblasts, and also human mesenchymal stem cells. Only fresh C60 films had a decreased number of initially adhering cells, with less spreading, growth, metabolic activity and viability, though no DNA damage was detected. Nanocrystalline diamond films proved to be excellent substrates for cell adhesion, growth and osteogenic differentiation, and this cell behavior was further improved by boron doping (concentration of 133–6700 ppm) or by oxygen termination of these films. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>